Nitric oxide as a source for bacterial triazole biosynthesis - Guiyun Zhao (Nature Portfolio, 2020)
How nature creates 1,2,3-triazole ring is a relevant question to N-N bond biosynthesis. Here, the authors report the biosynthetic route to the triazole-bearing antimetabolite 8-azaguanine and reveal that this can be assembled through an enzymatic and non-enzymatic cascade, in which nitric oxide is used as a building block.